Peningkatan Hasil Belajar Siswa Sekolah Dasar Melalui Aktivitas Pembelajaran Mengamati Berbantuan Audiovisual - Jampel, I Nyoman; Puspita, Kadek Riza (International Journal of Elementary Education, 2017)
This experimental study aims to determine the effect of audiovisual aided observational learning activities in a scientific approach to student learning outcomes. The population of this research is all students of class V in pioneering primary school 2013 in Buleleng district which amounted to 330 students. The sample was determined using random sampling technique on 63 students. Research design using Post Test Only Control Group Design. Data collection using interview method, observation, documentation and test, but data analyzed that is test. The student test scores were the post-test average score for the experimental class of 29.25 and the control class of 22.45 which was then analyzed by t-test for independent sample with the polled variance formula so that t-calculated = 9,33 with relative effectiveness Amounted to 73.13%. T-test> t-table (9,33> 2,000). These results indicate that there is a significant effect of audiovisual -aided observation learning activities on the results of V grade students in SD Buleleng lesson year 2016/2017